UVB-311 nm phototherapy and NAD(+)/NADH metabolism in keratinocytes in patients with psoriasis - Małgorzata Bernacka; Agata Liszewska; Ewa Robak; Anna Woźniacka; Jarosław Bogaczewicz (Termedia Publishing House, 2019)
Narrow band (311 nm) UVB phototherapy is established treatment for psoriasis. DNA is a target for UVB via formation of cyclobutane pyrimidine dimers, which trigger loss of dendritic cells and macrophages, and inhibit CD4+ and CD8+ T cells. UV causes the formation of thymine dimers, which activate nuclear enzyme poly(ADP-ribose) polymerase. The fact that poly(ADP-ribose) polymerase utilizes nicotinamide-adenine dinucleotide (NAD) explains NAD decreases after UV irradiation. NADH regulates transcriptional repressor carboxyl-terminal binding protein, whereas NAD(+) is a co-substrate in deacylation reactions, engaged in genomic silencing. Hyperproliferation of psoriatic keratinocytes requires NADH during oxidative phosphorylation. In one study the NADH fluorescence (reflecting NADH amount) was reduced in psoriatic lesions. NAD(+) used topically was as effective as 0.1% anthralin. Spectrophotometry enables real-time measurements of NADH fluorescence in vivo in the epidermis and points out a new direction for application of biophysics in medicine.